PERAN KIAI DALAM MENINGKATKAN KECERDASAN SPIRITUAL (SQ) SANTRI PONDOK PESANTREN AL I’ANAH WONOSOBO - Susiah Susiah; Maryono Maryono (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UNSIQ Jawa Tengah, 2021)
This research were aimed to; 1) know role of kiai had increased of the spiritual quotient of santri at the al ianah islamic boarding school, 2) know strategy of kiai had increased the spiritual quotient of santri the al i’anah islamic boarding school, 3) know the factor of handicaps that kiai increased the spiritual quotient of santri the al i’anah islamic boarding school. This research was used the qualitative approach. Subject of research included the kiai, santri, and head of santri. Technique of data collection were used observation, interview and data study. Test of data validation used the traingulation technique and technique of data analysis used interactive analysisi of miles and huberman that included data collection, data reduction, data display, and verifying:conclution. The result of research suc as that the role of kiai had increased the spiritual quotient include as a pedagog of islamic boarding school, as a second parent of santri. Kiai has strategies in increasing the spritual quotient of santri such as giving a insight thorough religious activity included activity of islamic studies, together praying, reading the holy of al quran, and making a devotional visit to a sacred place, and there is a warning if the santri has mistake.